2020
DOI: 10.3390/particles3010006
|View full text |Cite
|
Sign up to set email alerts
|

Dense Baryonic Matter and Applications of QCD Phase Diagram Dualities

Abstract: Recently it has been found that quantum chromodynamics (QCD) phase diagram possesses a duality between chiral symmetry breaking and pion condensation. For the first time this was revealed in the QCD motivated toy model. Then it was demonstrated in effective models as well and new additional dualities being found. We briefly recap the main features of this story and then discuss its applications as a tool to explore the QCD phase structure. The most appealing application is the possibility of getting the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 125 publications
(182 reference statements)
1
21
0
Order By: Relevance
“…Numerous lattice attempts to overcome the sign problem provide reliable information only in the region of small baryon density [2]. In the absence of straightforward results from lattice simulation of QCD, one applies different analytical approaches to study the ðμ; TÞ phase diagram: mean field approaches [3][4][5][6][7][8][9], the method of Dyson-Schwinger equations and the renormalization group [10][11][12][13], the large-N c approach [14], perturbative QCD [15,16] and others. Although the results obtained theoretically are important, it is rather difficult to estimate the reliability of these predictions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous lattice attempts to overcome the sign problem provide reliable information only in the region of small baryon density [2]. In the absence of straightforward results from lattice simulation of QCD, one applies different analytical approaches to study the ðμ; TÞ phase diagram: mean field approaches [3][4][5][6][7][8][9], the method of Dyson-Schwinger equations and the renormalization group [10][11][12][13], the large-N c approach [14], perturbative QCD [15,16] and others. Although the results obtained theoretically are important, it is rather difficult to estimate the reliability of these predictions.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio m 2 π Σ qq =μ 2 as a function of chemical potential, where Σ qq is defined in (7).FIG. 6.The ratio −hδð ⃗ E a Þ 2 i=T 4 , defined in(8), as a function of chemical potential. The minus sign is taken since the chromoelectric field decreases in dense matter as compared to the vacuum value.FIG.…”
mentioning
confidence: 99%
“…However, there is another mechanism of chiral asymmetry, which can be realized in dense quark matter in strong magnetic fields (see the discussion in Introduction) and is characterized by the chiral isospin chemical potential µ I5 . And it was shown that chiral isospin imbalance (when µ I5 = 0) promotes the generation of the charged PC phenomenon in dense quark matter [49][50][51][66][67][68][69][70] (see also the recent reviews [7,8] on the topic). Of course, this result can be trusted in the region of relatively low baryon densities of quark matter.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, interest in the phenomena occurring in dense baryonic matter serves as a trigger for studying QCD-like models and/or theories that are free from the above disadvantages and contribute to a deeper understanding of the properties of the phase diagram of matter at nonzero temperature and baryon density. Among such theories, for example, there are Nambu-Jona-Lasinio (NJL)-like models [1] (see also the reviews [2][3][4][5][6][7][8] and references therein), the QCD and QCD-like models with two-color quarks [9][10][11][12][13][14][15][16][17][18][19][20][21], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation